Thomas & friends. Ultimate friendship adventures [videorecording (DVD)] (Universal Pictures Home Entertainment, 2016)
10 action packed stories! All aboard for exciting rescues, engines tuning up, and flocks of new friends. Learn how to work together, build new friendships and rid the roads or rails for a rainbow of adventure!